Split 2 housing developments planned from 1957 to 1968 - Marinović, Hrvoje (Array, 2021)
Split 2 is a significant part of urban and architectural heritage in Split and Croatia. This arises from the scope and reach of the rational urban planning and use of space, inventive architectural design focused on construction technologies, operations and materials which were mainly organized in concentric construction sites of housing developments and areas which predominantly featured standardized residential buildings and residential high-rises in the period from 1957 to 1968.